The Virus and the Tree - Wilson, Alexander (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Alexander Wilson Title (English): The Virus and the Tree Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 74-77 Page Count: 4 Citation (English): Alexander Wilson, “The Virus and the Tree,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 74-77.